Consequences of Some Employment-Related Policies for National Wealth of a Transition Economy - Kurowski, Lech (Ekonomika, 2008)
National wealth, understood as a sum of natural capital, produced assets and human resources, plays a growing role in the globalized economy. Wealth at the disposal of the country’s subjects is an important condition for the long-term growth and development of individual countries. In the processes of globalization, the main actors be it multinational corporations or individual countries, are seeking control over those resources to get foothold in the new international division of labour. National wealth is also important for consumption. The feeling of being rich stimulates consumption, spending without bothering about the future. Loss of wealth has the opposite consequences in the longer perspective.Transition processes in Central and Eastern Europe brought about important transfers of wealth among different countries. Improved consumption levels thanks to, among others, unemployment and foreign debt are just some of the consequences of transition. The paper investigates the effects of transition processes on national wealth and speculates about long-term sustainability of the present Polish human resources-related policies.